374. THE ROLE OF EARLY MOBILIZATION AFTER ESOPHAGEAL CANCER SURGERY. (24th September 2022) - Schuring, Nannet; Geelen, SJG; van Berge Henegouwen, MI; Steenhuizen, SCM; van der Schaaf, M; van der Leeden, M; Gisbertz, SS
Abstract: A key component of the Enhanced Recovery After Surgery pathway for esophagectomy is early mobilization. Evidence on a specific protocol of early and structured mobilization is scarce, which explains variation in clinical practice. This study aims to describe and evaluate the early mobilization practice after esophagectomy for cancer in a tertiary referral center in the Netherlands. This retrospective cohort study included data from a prospectively maintained database of patients who underwent an esophagectomy between 01-01-2015 and 01-01-2020. Early mobilization entailed increase in activity with the first target of ambulating 100 meters. Primary outcomes were the number of postoperative days (PODs) until achieving this target and the reasons for not achieving this target. Secondary outcomes were the relationship between preoperative factors (e.g. Sex, BMI, ASA-score) and achieving the target on POD1, and the relationship between achieving the target on POD1 and postoperative outcomes (e.g. readmissions, postoperative complications). In total 384 patients were included. The median POD of achieving the target was 2 (IQR 1-3), with 173 (45.1%) patients achieving this on POD1. Main reasons for not achieving the target on POD1 was due to hemodynamic instability (22.7%). Male sex was associated with achieving the target on POD1 (OR = 2.08, p = 0.007); achieving the target on POD1 was not associated with postoperative outcomes. Ambulation up to 100 m on POD1 is achievable in patients after esophagectomy, with men having higher odds for achieving this target. No relationship between early mobilization and postoperative outcomes was found, however it may have effect on other parameters, such as improved long-term recovery, this should be investigated further in a larger patient cohort. ERAS pathways focusing on esophagectomy care are encouraged to incorporate 100 m ambulation on POD1 in their guideline as first postoperative target.